Environmental Democratisation: Assessing the Impact of Democratisation on Environmental Capacity in South and Southeastern Europe - O'Brien, T (Sage, 2014)
While a connection between democratic political systems and state environmental capacity has been established, the effects of democratisation on environmental capacity are less clear. The paper considers the relationship between democratisation and environmental capacity in Spain, Portugal, Bulgaria and Romania. All saw improvements in environmental capacity during democratisation, aided by the EU, but there are areas where capacity remains weak. These cases provide an opportunity to consider how different regime type (authoritarian and totalitarian) and mode of transition (negotiated and convulsive) enhance or restrict the development of environmental capacity. The paper argues that clear benefits for environmental capacity do arise from democratisation; however these advances are restricted by the continuation of attitudes and practices (legacies) from the non-democratic period. It also argues that variations in regime type and mode of transition have little impact on the development of environmental capacity